2022
DOI: 10.1038/s41375-022-01591-4
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance therapy for acute lymphoblastic leukemia: basic science and clinical translations

Abstract: Maintenance therapy (MT) with oral methotrexate (MTX) and 6-mercaptopurine (6-MP) is essential for the cure of acute lymphoblastic leukemia (ALL). MTX and 6-MP interfere with nucleotide synthesis and salvage pathways. The primary cytotoxic mechanism involves the incorporation of thioguanine nucleotides (TGNs) into DNA (as DNA-TG), which may be enhanced by the inhibition of de novo purine synthesis by other MTX/6-MP metabolites. Co-medication during MT is common. Although Pneumocystis jirovecii prophylaxis appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 100 publications
0
46
0
Order By: Relevance
“…Importantly, 6-MP is also metabolized to thioinosinate and 6-methylthioinosinate, which inhibit other aspects of purine biosynthesis including glutamine-5-phosphoribosylpyrophosphate amidotransferase, adenylosuccinate synthase, and IMP dehydrogenase (Extended Data Fig. 11c) 35 . It is likely that fumarate accumulation renders cells more sensitive to 6-MP due to: 1) a necessary reliance on the purine salvage pathway resulting from the fumarate-driven reversal of ADSL enzymatic activity, and/or 2) increased nucleoside uptake and metabolism, including 6-MP.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, 6-MP is also metabolized to thioinosinate and 6-methylthioinosinate, which inhibit other aspects of purine biosynthesis including glutamine-5-phosphoribosylpyrophosphate amidotransferase, adenylosuccinate synthase, and IMP dehydrogenase (Extended Data Fig. 11c) 35 . It is likely that fumarate accumulation renders cells more sensitive to 6-MP due to: 1) a necessary reliance on the purine salvage pathway resulting from the fumarate-driven reversal of ADSL enzymatic activity, and/or 2) increased nucleoside uptake and metabolism, including 6-MP.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler ultrasound is also helpful for the diagnosis of HSOS, including hepatomegaly, splenomegaly, ascites, thickening of gallbladder wall, elevated resistance index of hepatic artery, and blood reflux signal in portal vein. In recent years, the clinical use of multislice spiral CT combined with MPR and liver CTA imaging is helpful to the differential diagnosis and clinical evaluation of HSOS [ 43 ]. Most of the reversible HVOD patients in the American CCG-1952 test have only HSOS manifestations and do not have mature clinical manifestations of HVOD or meet the pathological diagnostic criteria [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The daunting challenge is now to reduce treatment intensity to diminish side effects and avoid ensuing long-term sequelae without endangering the hitherto achieved excellent overall treatment outcome. Some of the trials that have addressed this issue so far have been quite successful (even without utilizing any genetic risk score), whereas those trials which reduced the duration of maintenance therapy to 6 months were not, at least as regards HD ALL [55,117,[122][123][124][125]. Although Kato et al found that one year of maintenance therapy is probably sufficient for TCF3::PBX1-and ETV6::RUNX1-positive cases, it is definitely not adequate for all HD leukemias.…”
Section: Diagnostic Assessment Disease Stratification and Treatment O...mentioning
confidence: 99%